On Weak Forms of Upper and Lower Continuous Multifunctions between an Ideal Topological Space and a Bitopological Space (European Journal of Pure and Applied Mathematics, 2025)
This paper presents new concepts of continuous multifunctions defined from an ideal topological space into a bitopological space, called upper weakly $τ^\star(σ_1,σ_2)$-continuous multifunctions and lower weakly $τ^\star(σ_1,σ_2)$-continuous multifunctions. Furthermore, several characterizations and some properties concerning upper weakly $τ^\star(σ_1,σ_2)$-continuous multifunctions and lower weakly $τ^\star(σ_1,σ_2)$-continuous multifunctions are investigated. Moreover, the relationships between almost $τ^\star(σ_1,σ_2)$-continuity andweak $τ^\star(σ_1,σ_2)$-continuity are established.
Keywords: upper weakly $τ^\star(σ_1,σ_2)$-continuous multifunction; lower weakly $τ^\star(σ_1,σ_2)$-continuous multifunction